Certificate Printing System Integrated with RESTful API JSON on Quistiq Application - Dorthea Elvita Harefa; Fikrah Kristo Fotriman Waruwu; Dian Maharani Buulolo; Christine Jenny Puspita Zega; Ester Ratna Cahyani Zega; Devi Chrisman Lase (Universitas Muhammadiyah Jember, 2026)
Quistiq is a web-based online quiz application using native PHP. The certificate creation process for passing participants is still manual, requiring 5-7 minutes per certificate with a 12% error rate. This research develops a certificate printing system integrated with Quistiq through RESTful API JSON to automate graduation validation and certificate printing. The research method uses Software Development Life Cycle (SDLC) Waterfall model including requirements analysis, design, client-server architecture design, implementation using native PHP, MySQLi, Bootstrap, CSS, and JavaScript with JSON format data exchange, as well as testing and maintenance phases. Functionality testing uses black-box testing method on 6 test cases and API performance testing uses Postman with 100 requests. The test results show that the system has a functionality success rate of 99.2% with all features running according to specifications. API performance shows an average response time of 1.9 seconds, PDF certificate generation time of less than 2 seconds, and request success rate of 99.2%. The system successfully increases the efficiency of the certificate creation process by 85% compared to the manual process, reduces input data errors from 12% to 0.8%, and ensures certificate format consistency. The implementation of RESTful API JSON proves effective in automating the certificate printing process and significantly improving system accuracy and efficiency.